PENGARUH KEPUASAN KERJA, MOTIVASI DAN REWARD TERHADAP KINERJA KARYAWAN CV. KRISNA DESA WISATA BLANGSINGA - Ni Kadek Mea Wandari; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
Krisna Desa Wisata Blangsinga (Krisna Oleh-Oleh Khas Bali) is a private company engaged in the sale of Balinese souvenirs that offers a variety of attractive Balinese products in the form of various designs of cartoon T-Shirts about Bali which are produced by themselves. There are several phenomena of employee performance that can be seen from the attitude of the employees themselves since the implementation of rolling work due to the Covid-19 pandemic from March 2020 until now. Indications of this decline in employee performance can be illustrated by notes from personnel that some employees are starting to like to be late for work, lazy to work, not wearing uniforms according to schedule, often asking for sudden permission, leaving work hours and there are even some employees who submit resignation letters so that make many consumers move to other stores due to poor service, which consequently makes CV sales. Krisna Blangsinga Tourism Village is declining, of course this will have a bad impact if it continues. This study aims to examine and obtain empirical evidence of the effect of job satisfaction, motivation and reward on employee performance at CV. Krisna Blangsinga Tourism Village. The population in this study were all employees of CV. Krisna Blangsinga Tourism Village as many as 38 people.The results of this study indicate that job satisfaction, motivation and reward have a positive and significant effect on employee performance at CV. Krisna Blangsinga Tourism Village. Suggested to CV. Krisna Blangsinga Tourism Village to give more encouragement to employees in doing a good job and make the company proud.